Gembala Yang Baik Sebagai Kerangka Teologi Pastoral (Konstruksi Teologi Pastoral di GKPI Melalui Pendekatan Philos dan Ginosko dalam Yohanes 10:11,14 Sebagai Langkah Perawatan Komunitas Bergereja) - Hutasoit, Irvan; Sianipar, Lasti Rani (Jurnal Teologi Cultivation, 2024)
For too long, churches have understood Pastoral Care only as a mentoring activity for their members so that the frame of Pastoral Theology does not accompany the mentoring steps. This paper will propose a Pastoral Theology that frames all Pastoral assistance for congregation members. Moving on from the theme of the GKPI Strategic Plan (Renstra) in 2024, the authors will make the phrase Good Shepherd in John 10:11,14 as the basic idea for proposing Pastoral Theology by referring to two important words, namely philos and ginosko. This paper will use qualitative research to construct philos and ginosko so that both become Pastoral Theology that frames the church's ministry. In the end, the author proposes that Pastoral Theology is the care of the church community.